Pelatihan Coaching Clinic Festival FIFA Grassroots Pelatih Sepakbola Se- Kabupaten 50 Kota - Emral Emral; Alex Aldha Yudi (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2021)
The problem of understanding the knowledge and methods of training in the grassroots age, there are still many coaches in the 50 City District who do not understand the development of early childhood football, even with many adequate facilities and equipment but many collide with the lack of experience of the coaches in developing training methods, principles. - principles and forms of exercise in training children at an early age. Of course this makes it difficult to achieve quality in the development of children's play and achieve the goals that have been set by PSSI and FIFA in achieving football achievements and development at an early age. For that, a solution is needed through the Training of the FIFA Grassroots Festival Coaching Clinic Football Coach in 50 Cities. The problem formulation is as follows: (a) Lack of understanding of district trainers. 50 Cities in developing training methods (b) Lack of knowledge of district trainers. 50 Cities about the concepts and principles of training (c) Lack of knowledge and understanding of district trainers. 50 Cities in managing the training (d) Lack of knowledge of district trainers. 50 Cities in developing training programs and models. The target audience. In this activity, 30 SSB trainers from 50 Cities Districts. Implementation of the 2020 Grassroots Fesitival FIFA Grassroots Coach Coaching Clinic Training, which is located in the District. 50 Cities.